Prognostic impact of retropharyngeal lymphadenopathy in early-stage HPV-associated oropharyngeal cancer: Implications for staging optimization. (March 2021) - Bhattasali, Onita; Torres, Fernando A.; Kang, Hyung K.; Thompson, Lester D.R.; Abdalla, Iman A.; McNicoll, Michael P.; Lin, Alice; Ryoo, Joan J.; Chen, Jergin; Iganej, Shawn
Highlights: RPL is not considered in staging of HPV-associated OPSCC. This study found that RPL independently predicted for inferior outcomes. Receipt of high-dose cisplatin may have mitigated the negative impact of RPL on LRR. Abstract: Objectives: We analyzed the prognostic impact of retropharyngeal lymphadenopathy (RPL) in stage I node-positive HPV-associated oropharyngeal squamous cell carcinoma (OPSCC). Materials and Methods: We performed a centralized and blinded radiographic review of the pre-treatment images of 234 consecutive patients with AJCC 8th edition stage I cT1-2N1 HPV-associated OPSCC treated with definitive chemoradiation from 2006 to 2016. Five-year disease control and survival outcomes were reported. The prognostic significance of RPL was evaluated through multivariable analysis adjusting for age, smoking history (<10 vs. >10 pack-years), and systemic regimen received. Results: Median follow-up for surviving patients was 49 months (range: 16–121). RPL was associated with increased locoregional recurrence (LRR) (17.0% v. 3.4%, p = 0.01) and distant metastasis (DM) (29.1% v. 5.9%, p = 0.001) and inferior progression-free survival (PFS) (55.6% v. 88.2%, p < 0.001) and overall survival (OS) (60.6% v. 91.2%, p < 0.001). In stage I patients who did not receive high-dose cisplatin (HDC), RPL was associated with worse LRR (p = 0.04), DM (p = 0.03), PFS (p < 0.001), and OS (p < 0.001), whereas in those who did receive HDC, RPL was only associated with increased DM (p = 0.002) and inferior PFS (p = 0.04). Conclusion: This study suggests that RPL portends a poor prognosis in stage I node-positive HPV-associated OPSCC. The negative impact on LRR may have been mitigated by receipt of HDC. Outcomes of stage I disease with RPL were comparable to historical reports of patients with more advanced-stage disease. Incorporation of RPL into future disease staging should be considered in order to optimize risk-stratification and exclude unsuitable candidates from treatment de-intensification efforts.